Manajemen Pendidikan Madrasah Aliyah Muhammadiyah Serpong Tangerang Selatan - Nuraeni, Heni Ani (Program Studi Pendidikan Ekonomi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Prof. DR. HAMKA, 2016)
Research intended to acknowledge managerial aspects of Madrasah Aliyah Muhammadiyah Serpong Tangerang Selatan, especially from the aspects of planning, organizing, actuating, and controlling. The research method used was the qualitative explorative method. Data collected from observation, documents analysis, and in-depth interview with some teachers. Data triangulation used as data analysis tool by compounding the data from observation, interviews and document analysis. The study result showed that overall the management function performed well from the aspect of planning, organizing, actuating, and controlling. Planning function recommended to have specific programs, not only actuate the main program commanded by Ministry of Religious Affair, to make it more known by people at Tangerang Selatan district.